The Effect of Audiovisual Media Counseling on Menopause on The Level of Knowledge in Perimenopause - Sukmanawati, Dera; Isnaeni, Khurairoh (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Menopause is one of the stages of life that will inevitably be experienced by all women. Menopause begins with premenopause, during this period there is a decreased estrogen and progesterone hormones with demanding adjustments to physical and lifestyle changes that can cause health problems. Complaints during menopause both physical and psychological will be experienced by women during menopause, lack of information causes menopause women to be unable to overcome their complaints. Efforts to increase knowledge about menopause can be done with Audiovisual counseling. The purpose of research is to determine the effect of counseling on menopause on the knowledge of perimenopause. This research used a quantitative research method with one group pre test and post test design. The sample in this study was all women aged 50 years and over who came to Posbindu Cipasung Village, Darma District, Kuningan Regency as many as 47 respondents. This research instrument used a questionnaire. Data analysis was univariate and bivariate (Wilcoxon test). The results showed that the average level of knowledge of perimenopausal women before being given counseling was 63.40. The average level of knowledge of perimenopausal women after counseling was 90.21. The results of data analysis obtained ρ-value of 0.000 (<0.05). There is an effect of counseling on knowledge about menopause in perimenopausal women at Posbindu Cipasung Village, Darma District, Kuningan Regency. Audiovisual counseling is expected to be sustainable and can be used as a reference or reference material to further improve counseling about menopause.><0.05). There is an effect of counseling on knowledge about menopause in perimenopausal women at Posbindu Cipasung Village, Darma District, Kuningan Regency. Audiovisual counseling is expected to be sustainable and can be used as a reference or reference material to further improve counseling about menopause